1999
DOI: 10.1097/00000539-199907000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Emergence from Anesthesia and Incidence of Vomiting with Remifentanil in a Pediatric Population

Abstract: A randomized, controlled clinical trial of 115 patients undergoing dental restoration indicated that an anesthetic technique using remifentanil provided quality of emergence comparable to and no greater incidence of vomiting than a nonopiate technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…When comparing remifentanil and alfentanil, there was no significant difference between the incidence of POV (31% vs. 26%) in strabismus surgery (7). Comparing the groups with and without remifentanil under desflurane anesthesia, the incidence of POV was not different even though the administration of desflurane was different (8). Oh et al ( 9) evaluated the incidence of PONV after pediatric strabismus surgery with sevoflurane or remifentanil-sevoflurane, both using 50% N 2 O/O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…When comparing remifentanil and alfentanil, there was no significant difference between the incidence of POV (31% vs. 26%) in strabismus surgery (7). Comparing the groups with and without remifentanil under desflurane anesthesia, the incidence of POV was not different even though the administration of desflurane was different (8). Oh et al ( 9) evaluated the incidence of PONV after pediatric strabismus surgery with sevoflurane or remifentanil-sevoflurane, both using 50% N 2 O/O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…For example, one study reported that the side effects of remifentanil were not more than nonopioid drugs. [ 23 ] While others demonstrated that complications such as breathing and conscious reduction were observed in the use of remifentanil. [ 8 9 ] The combination of remifentanil with midazolam increases forgetfulness after the procedure compared to midazolam alone.…”
Section: Discussionmentioning
confidence: 99%
“…Es wird von unspezifischen Plasma-und Gewebsesterasen metabolisiert und zeigt bei Erwachenen Plasmaeliminationshalbwertszeiten von 3-10 min. Es ist für Kinder ab einem Jahr zugelassen und über seine Anwendung bei pädiatrischen Narkosen liegen eine Reihe von Studien vor [8,13,14,15,28,71,99,100]. Seine Eliminationshalbwertszeit entspricht der von Erwachsenen [14], und es scheint auch nach längerer Anwendung nicht zu kumulieren.…”
Section: Opioideunclassified